Capsular imbrication for posttraumatic instability of the distal radioulnar joint - Manz, Stefanie; Wolf, Maya Barbara; Leclère, Franck Marie; Hahn, Peter; Bruckner, Thomas; Unglaub, Frank (The journal of hand surgery. [American volume], 2011)
Purpose - To analyze functional and subjective outcomes of patients with posttraumatic dorsal instability of the distal radioulnar joint (DRUJ) treated by a dorsal capsular imbrication. - Methods - We reviewed 11 patients (7 men and 4 women) with posttraumatic instability of the DRUJ who were treated by a capsular imbrication. The patients ranged in age from 18 to 48 years (average, 33 y). The duration of symptoms before surgery ranged from 3 weeks to 6 months (average, 5 mo). We evaluated subjective outcome measurements such as the Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire, questions regarding symptoms of pain and instability, and overall satisfaction. Objective outcome measurements were physical examination, standard radiographs, and a review of any surgical complications. Patients were asked whether they experienced wrist tenderness with applied pressure, swelling, scar sensitivity, or pain. We determined functional outcome using the Modified Mayo Wrist Score including range of motion and grip strength. The score was used to evaluate the surgical technique and enable comparison with other surgical methods used to treat instability of the DRUJ. - Results - After surgery, the total mean DASH score was 15 points. Range of motion, grip strength, pain, and overall function resulted in a mean Modified Mayo Wrist Score of 88 points, and therefore a good functional outcome. Three patients were noted to have persistent mild DRUJ instability on the stress test but did not have symptoms. The only intraoperative or postoperative complications observed were transient paresthesias on the ulnar side of the hand. - Conclusions - Capsular imbrication for posttraumatic instability of the DRUJ is a highly effective procedure with few complications and good functional and subjective results even in cases with concomitant healed fractures of the radius or ulnar styloid. - Type of study/level of evidence - Therapeutic IV.